Pengaruh Soft Skill, Hard Skill Dan Motivasi Pada Kesiapan Kerja Mahasiswa Sebagai Generasi Z Dalam Menghadapi Era Digital - Riyanti Maulidiyah; Hasan Ubaidillah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The development of technology towards everything digital is currently increasingly rapid. The digital era causes humans to use it continuosly as a lifestyle and technology as the main intermediary. Hard skills are technical and academic skills that can be obtained from formal education such as school, college and training. Soft skills are skills and abilities that are born within in everyday life. Motivation for students in important. By having motivation, students will have the enthusiasm to carry out and achieve goals. Word readiness is a condition of maturity for students who want to enter the world of work after graduating from college without long training. This research aims to determine the result of the influence of soft skills, hard skill and motivation on student’s work readiness as generation Z in facing the digital era. The use of this method in research is a quantitative method with an influencing type of associative research, namely from three independent variables to one dependent variable. The source of data collection uses primary data obtained by distributing questionnaires to respondents via google form. Primary data management is carried out using soft skills, hard skills and motivation simulthaneously influence work readiness in the context that has been studied. Keywords: Soft Skills, Hard Skilsl, Motivation, Work Readiness